What determines earmarked funding to international development organizations?: evidence from the new multi-bi aid data - Eichenauer, Vera; Reinsberg, Bernhard (The review of international organizations, 2017)
Earmarked aid to international organizations has quadrupled over the last two decades and now represents almost 20% of total aid. This paper introduces a new dataset on earmarked aid, which alternatively has been referred to as multi-bi, restricted, non-core or trust fund aid. The data make it possible to track the rise of the new aid channel over an extended time period and in greater detail regarding, e.g., the implementing multilateral organizations. The data include more than 100,000 earmarked projects of 23 OECD donors to 290 multilateral institutions from 1990 to 2012. We graphically illustrate the patterns in earmarked aid for all actors: donor governments and their aid-providing agencies, multilateral organizations, and recipient countries. We also highlight promising research questions that can be analyzed with the multi-bi data. In a first empirical application of the data, we analyze four suggested donor motives for earmarked aid at the donor-recipient level. Contrary to donor claims, we find that earmarked aid and bilateral aid target the same recipients. We also find evidence that some donors use earmarked aid to bypass recipient countries with weak governance. Overall, our explorative analysis suggests that earmarked aid serves many purposes and that donors use it in different ways. This calls for more fine-grained research on the reasons and implications for earmarked aid.